Epoxy resin adhesive as well as preparation method and application thereof

By adding components such as ionic liquid, coupling agent and inorganic filler to the epoxy resin adhesive, the proportion and viscosity control of components are optimized, and the problem of insufficient bonding strength of existing power-on disassembled epoxy adhesives is solved, achieving high Combination of bonding strength and good removable properties.

CN119463771APending Publication Date: 2025-02-18XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767988.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing power-on disassembled epoxy adhesives have a large gap in the bond strength compared with traditional epoxy adhesives, which limits their promotion and use.

Method used

By adding ionic liquid, coupling agent, inorganic filler, and selected curing agent, toner and auxiliary agent to the epoxy resin adhesive, the viscosity of the epoxy resin is controlled within the range of 1000 to 15000 cps, and the component ratio is optimized to improve the viscosity of the adhesive. Connection strength and removable performance.

Benefits of technology

It achieves good electrical disassembly performance while maintaining high bonding strength, avoiding the impact of adhesive residue on electronic components recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169485270000111
    Figure BDA0005169485270000111
Patent Text Reader

Abstract

The invention belongs to the field of epoxy resin adhesives, and particularly relates to an epoxy resin adhesive as well as a preparation method and application thereof. The epoxy resin adhesive contains epoxy resin, ionic liquid, a coupling agent, inorganic filler and optional curing agent, toner and auxiliaries, the viscosity of the epoxy resin at the temperature of 25 DEG C is 1000-15000 cps, and the mass ratio of the epoxy resin to the ionic liquid to the coupling agent to the inorganic filler is 100: (20-200): (2-50): (120-600). The epoxy resin adhesive provided by the invention not only has an electrically detachable function, but also has relatively high bonding strength and a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of epoxy resin adhesives, and in particular relates to an epoxy resin adhesive and a preparation method and application thereof. Background Art

[0002] Epoxy adhesives mainly contain epoxy resin and curing agent. In addition to epoxy resin and curing agent, they may also contain auxiliary materials such as toughening agent, diluent, accelerator, coupling agent, etc. Epoxy adhesives have the advantages of strong corrosion resistance, good dielectric properties, and strong versatility. They are well-known in electronic products for their excellent bonding properties and versatility, and are known as "all-purpose glue" or "strong glue".

[0003] With the global requirements for environmental protection and energy conservation, many important electronic components need to disassemble some of the bonded parts for reassembly, repair and recycling in the actual production process. These applications usually require the adhesive to have detachable properties while maintaining a certain bonding strength. However, due to the strong bonding performance of epoxy adhesives, the surfaces of these used electronic components are attached with residual adhesives, which cannot be recycled, thus causing serious waste. In recent years, there is a technology that adds alkali metal salts and solvated matrix to epoxy adhesives to form liquid electrolytes, thereby giving epoxy adhesives the function of being disassembled under power-on conditions, thereby achieving gentle disassembly without damaging the electronic bonding substrate. However, although the existing power-on disassembleable epoxy adhesives have the function of being disassembled under power-on conditions, their bonding strength is still far behind that of traditional widely used epoxy adhesives, which limits the promotion and use of such electrical disassembly epoxy adhesives. Summary of the invention

[0004] The first object of the present invention is to provide an electrically detachable epoxy resin adhesive with high bonding strength in view of the disadvantage that the electrically detachable epoxy adhesive in the prior art has poor bonding strength.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned epoxy resin adhesive.

[0006] The third object of the present invention is to provide application of the above epoxy resin adhesive in bonding electronic products.

[0007] The epoxy resin adhesive provided by the present invention contains epoxy resin, ionic liquid, coupling agent, inorganic filler and optional curing agent, color powder and auxiliary agent. The viscosity of the epoxy resin at 25° C. is 1000-15000 cps, and the mass ratio of the epoxy resin, ionic liquid, coupling agent and inorganic filler is 100:(20-200):(2-50):(120-600).

[0008] The preparation method of the epoxy resin adhesive provided by the invention comprises the steps of uniformly mixing epoxy resin, ionic liquid, coupling agent, inorganic filler and optional curing agent, color powder and auxiliary agent to obtain the epoxy resin adhesive.

[0009] The key to the present invention is to add ionic liquid to the epoxy resin adhesive. On the one hand, the ionic liquid can undergo a Faraday reaction after being energized, and the ionic conductivity of the epoxy resin decreases less after being cured than when it is not cured, and has little effect on the ion migration ability of the cured system. It is speculated that this may be because ion migration is related to the dipole interaction between the dissociated ions and the polymer segments, and the movement of the polymer segments can help ion migration. Therefore, the liquid epoxy resin can still maintain good electrical disassembly performance after being cured. Introducing ionic liquid into the epoxy resin adhesive can give it electrical disassembly performance; on the other hand, On the other hand, ionic liquids can also act as curing agents during the curing process of epoxy resins, thereby enhancing the adhesion of the interface. However, this will also lead to an increase in the viscosity of the system, especially after the addition of inorganic fillers to the epoxy system, which poses a challenge to the uniformity of the dispersion of the inorganic fillers. By controlling the viscosity of the epoxy resin at 25°C to 1000-15000cps, the overall viscosity of the system can be reduced, which is beneficial to the initial dispersion of the inorganic fillers. At the same time, the presence of hydrogen bonds in the ionic liquid can make the inorganic fillers in the system more evenly dispersed, thereby effectively exerting the role of the inorganic fillers and improving the bonding strength. DETAILED DESCRIPTION

[0010] The epoxy resin adhesive provided by the present invention contains epoxy resin, ionic liquid, coupling agent, inorganic filler and optional curing agent, color powder and auxiliary agent. The mass ratio of the epoxy resin, ionic liquid, coupling agent and inorganic filler is 100: (20-200): (2-50): (120-600). Based on 100 parts by mass of the epoxy resin, the content of the ionic liquid is 20 to 200 parts by mass, such as 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 parts by mass or any value therebetween; the content of the coupling agent is 2 to 50 parts by mass, such as 2, 4, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50 parts by mass or any value therebetween; the content of the inorganic filler is 120 to 600 parts by mass, such as 120, 140, 160, 180, 200, 250, 300, 350, 400, 450, 500, 550, 600 parts by mass or any value therebetween. any value therebetween; the content of the curing agent is preferably 20-200 parts by mass, such as 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 parts by mass or any value therebetween; the content of the toner is preferably 0.4-50 parts by mass, such as 0.4, 1, 2, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50 parts by mass or any value therebetween; the content of the auxiliary agent is preferably 0-200 parts by mass, such as 0, 5, 10, 15, 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 parts by mass or any value therebetween.

[0011] In a preferred embodiment, the content of the epoxy resin is 10 to 25 parts by mass, such as 10, 12, 15, 18, 20, 22, 25 parts by mass or any value therebetween; the content of the ionic liquid is 5 to 20 parts by mass, such as 5, 8, 10, 12, 15, 18, 20 parts by mass or any value therebetween; the content of the coupling agent is 0.5 to 5 parts by mass, such as 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by mass or any value therebetween; the content of the inorganic filler is 30 to 60 parts by mass, such as 30 , 35, 40, 45, 50, 55, 60 parts by mass or any value therebetween; the content of the curing agent is 5 to 20 parts by mass, such as 5, 8, 10, 12, 15, 18, 20 parts by mass or any value therebetween; the content of the toner is 0.1 to 5 parts by mass, such as 0.1, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by mass or any value therebetween; the content of the auxiliary agent is 0 to 20 parts by mass, such as 0, 1, 3, 5, 8, 10, 12, 15, 18, 20 parts by mass or any value therebetween.

[0012] In the present invention, the epoxy resin may be an aliphatic epoxy resin having two or more epoxy groups, or an aromatic epoxy resin having two or more epoxy groups, or a mixture of the two. The aliphatic epoxy resin having two or more epoxy groups may be at least one of an alicyclic epoxy resin, a glycidylamine epoxy resin, a hydantoin epoxy resin, an epoxy resin having a siloxane skeleton, and the like. Specific examples of the alicyclic epoxy resin include, but are not limited to, vinyl (3,4-cyclohexene) dioxide and / or 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-dioxane. The glycidylamine epoxy resin may be, for example, tetraglycidylbis(aminomethyl)cyclohexane. The hydantoin epoxy resin may be, for example, 1,3-diglycidyl-5-methyl-5-ethylhydantoin. The epoxy resin having a siloxane skeleton may be, for example, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane. The aromatic epoxy resin having more than two epoxy groups can be various existing epoxy resins with two epoxy groups and containing aromatic ring structures, and specific examples thereof include but are not limited to: at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, tetrabromobisphenol A epoxy resin, fluorene epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin, biphenyl epoxy resin, glycidylamine epoxy resin, naphthalene ring-containing epoxy resin, etc., and specifically at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, o-hydroxymethyl bisphenol A diglycidyl ether, dihydroxymethyl bisphenol A diglycidyl ether, tetrabromobisphenol A diglycidyl ether, resorcinol diglycidyl ether, pyrogallol triglycidyl ether and pentaerythritol diglycidyl ether can be cited. In addition, the viscosity of the epoxy resin at 25° C. needs to be controlled in the range of 1000 to 15000 cps, such as 1000 cps, 2000 cps, 3000 cps, 4000 cps, 5000 cps, 8000 cps, 10000 cps, 15000 cps or any value therebetween.

[0013] In the present invention, the melting point of the ionic liquid is preferably below 25°C, such as 25°C, 23°C, 20°C, 18°C, 15°C, 13°C, 10°C, 8°C, 5°C, 2°C, 0°C, -5°C, -10°C, -15°C, -20°C, -30°C, -40°C, etc. The ionic liquid is composed of cations and anions. The cations are preferably selected from at least one of imidazole cations, pyrrole cations, quaternary ammonium salt cations, quaternary phosphonium salt cations, pyrrolidine cations and piperidine cations. The anions are preferably selected from at least one of trifluoromethanesulfonate anions, tetrafluoroborate anions, hexafluorophosphate anions, bisfluoromethanesulfonyl imide anions, hydrogen sulfate anions, ethyl sulfate anions and p-toluenesulfonate anions. Specific examples of the above-mentioned ionic liquids include, but are not limited to: 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-2,3-dimethylimidazolium trifluoromethanesulfonate, 1-octyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-2,3-dimethylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonate), 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonate), 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-3- ... at least one of bis(trifluoromethanesulfonyl)imide salts, 1,3-diethylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide salts, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salts, N-butylpyridinium tetrafluoroborate, hexyltriethylammonium bis(trifluoromethanesulfonyl)imide salts, methyltrioctylphosphonium bis(trifluoromethanesulfonyl)imide salts, N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salts, N-butyl-N-methylpyrrolidine trifluoromethanesulfonate salts and N-propyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide salts.

[0014] In the present invention, the type and source of the coupling agent can be various existing options, and can be selected from at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanatesilane, and specific examples thereof include but are not limited to: at least one of γ-aminopropyl triethylsiloxane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-methacrylate propyl trimethoxysiloxane, γ-thiopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane. The addition of the coupling agent helps to promote the uniform dispersion of the inorganic filler in the epoxy adhesive system, thereby promoting the full performance of the inorganic filler.

[0015] In the present invention, the inorganic filler can be any existing material that can improve the heat resistance, moisture resistance, electrical conductivity, thermal conductivity and other properties of the epoxy adhesive, and can specifically include at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talcum powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder. The average particle size of the inorganic filler is preferably 0.1 to 10 μm, such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value therebetween. In addition, the surface of the inorganic filler is preferably treated with a silane coupling agent, which can improve the compatibility of the inorganic filler with the epoxy adhesive system, and is more conducive to the improvement of the various properties of the epoxy adhesive. The specific treatment method can be any existing conventional selection, which can be known to those skilled in the art and will not be repeated here.

[0016] In the present invention, the type and source of the curing agent can be various existing options, for example, it can be selected from at least one of amine curing agents, acid anhydride curing agents and imidazole curing agents. The amine curing agent can be listed as at least one of aliphatic polyamines, alicyclic polyamines, piperazine-type polyamines and aromatic polyamines. Among them, the aliphatic polyamine can be listed as at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, triethanolamine, dicyandiamide, triethylenetetramine, tetraethylenepentamine, meta-xylylenediamine, trimethylhexamethylenediamine, and 2-methylpentamethylenediamine. The alicyclic polyamine can be listed as at least one of isophoronediamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, and 1,2-diaminocyclohexane. The piperazine-type polyamine can be listed as N-aminoethylpiperazine and / or 1,4-bis(2-amino-2-methylpropyl)piperazine. The aromatic polyamines include at least one of diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-diamino-3,3'-diethyldiphenylmethane, bis(methylthio)toluenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenylsulfone, diethyltoluenediamine, trimethylenebis(4-aminobenzoate) and polytetramethylene oxide-diparaaminobenzoate. The anhydride curing agent includes at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, endomethyltetrahydrophthalic anhydride, alkenyl-substituted succinic anhydride, methylnadic anhydride and glutaric anhydride. Examples of the imidazole curing agent include 2-substituted imidazole compounds such as imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, and trimellitic acid imidazole salts such as 1-cyanoethyl-2-undecylimidazole. , at least one of triazine adducts such as 4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-dihydroxymethylimidazole.In addition, the optimal ratio of the curing agent is 0.6 to 1.3 equivalents relative to the epoxy equivalent of the epoxy resin.

[0017] In the present invention, the color powder can be any existing substance that can impart color to the epoxy adhesive without affecting its performance, and can be specifically selected from at least one of carbon black, iron oxide color powder, chromate color powder, cadmium color powder, ultramarine and phthalocyanine blue. Among them, the iron oxide color powder can be at least one of iron yellow, iron red and iron black. The chromate color powder can be chrome yellow and / or chrome green. The cadmium color powder can be cadmium red and / or cadmium yellow.

[0018] In the present invention, the type of the auxiliary agent is not particularly limited, and for example, the auxiliary agent may be selected from at least one of a defoaming agent, a leveling agent, a dispersant, and an antioxidant.

[0019] The preparation method of the epoxy resin adhesive provided by the present invention comprises uniformly mixing epoxy resin, ionic liquid, coupling agent, inorganic filler, and optional curing agent, color powder and auxiliary agent to obtain epoxy resin adhesive. In a preferred embodiment, the mixing method specifically comprises the following steps: uniformly mixing epoxy resin, ionic liquid and coupling agent, and optional curing agent, color powder and auxiliary agent in a container by scraping the wall, adding inorganic filler to the obtained mixture and continuing to scrape the wall to mix uniformly, passing the obtained mixture through three rollers twice, and then transferring to a double planetary hybrid stirring kettle for stirring and mixing, and then vacuuming and degassing the obtained mixture, and sealing and storing it for later use after discharging.

[0020] The present invention will be described in detail below by way of examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0021] In the following embodiments and comparative examples, the raw materials and sources of the epoxy resin are as follows: bisphenol F diglycidyl ether, purchased from Mitsubishi Chemical, brand 806, with a viscosity of 2300 cps at 25°C; bisphenol A diglycidyl ether, purchased from Mitsubishi Chemical, brand 828, with a viscosity of 1800 cps at 25°C; bisphenol F diglycidyl ether, purchased from CVC, brand RF1320, with a viscosity of 35000 cps at 25°C.

[0022] In the following examples and comparative examples, carbon black was purchased from Mitsubishi Chemical with a brand name of MA100; calcium carbonate was purchased from Jiangxi Hengshengtai New Materials with a brand name of HST-8101; and kaolin powder was purchased from Haibaishun Biotechnology with a brand name of K100129.

[0023] Example 1

[0024] 25 parts by mass of bisphenol F diglycidyl ether 806, 20 parts by mass of 1-butyl-3-methylimidazole trifluoromethanesulfonate, 0.5 parts by mass of γ-aminopropyl triethylsiloxane, 20 parts by mass of m-phenylenediamine, and 0.5 parts by mass of carbon black are scraped and mixed evenly in a container, 60 parts by mass of silicon dioxide are added to the obtained mixture, the wall is scraped and mixed evenly, and then the mixture is passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall is scraped when the stirring time is 15 minutes, and then the material is discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0025] Example 2

[0026] 10 parts by mass of bisphenol F diglycidyl ether 806, 5 parts by mass of 1-ethyl-3-methylimidazole trifluoromethanesulfonate, 0.5 parts by mass of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 9 parts by mass of m-phenylenediamine, and 0.5 parts by mass of carbon black were scraped and mixed evenly in a container, 50 parts by mass of silicon dioxide were added to the obtained mixture, the wall was scraped and mixed evenly, and then passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes, and then the material was discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0027] Example 3

[0028] 15 parts by mass of bisphenol F diglycidyl ether 806, 10 parts by mass of 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 0.5 parts by mass of γ-thiopropyl trimethoxysiloxane, 15 parts by mass of meta-phenylenediamine, and 0.5 parts by mass of carbon black were scraped and mixed evenly in a container, 30 parts by mass of silicon dioxide were added to the obtained mixture, the mixture was continued to be scraped and mixed evenly, and then passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes, and then the material was discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0029] Example 4

[0030] 23 parts by mass of bisphenol F diglycidyl ether 806, 10 parts by mass of 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt, 0.5 parts by mass of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, 7 parts by mass of m-phenylenediamine, and 0.5 parts by mass of carbon black were scraped and mixed evenly in a container, 50 parts by mass of silicon dioxide were added to the obtained mixture, the wall was scraped and mixed evenly, and then passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes, and then the material was discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0031] Example 5

[0032] 25 parts by mass of bisphenol A diglycidyl ether 828, 10 parts by mass of N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, 0.5 parts by mass of aniline methyl triethoxysilane, 9 parts by mass of m-phenylenediamine, and 0.5 parts by mass of carbon black were scraped and mixed evenly in a container, 50 parts by mass of silicon dioxide were added to the obtained mixture, the wall was scraped and mixed evenly, and then passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes, and then the material was discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0033] Example 6

[0034] 25 parts by mass of resorcinol diglycidyl ether, 10 parts by mass of 1-butyl-3-methylimidazole trifluoromethanesulfonate, 0.5 parts by mass of γ-aminopropyl triethylsiloxane, 9 parts by mass of meta-phenylenediamine, and 0.5 parts by mass of carbon black were scraped and mixed evenly in a container, 50 parts by mass of silicon dioxide were added to the obtained mixture, the mixture was continued to be scraped and mixed evenly, and then passed through three rollers twice, and then transferred to a double planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes, and then the material was discharged after vacuum degassing treatment to obtain an epoxy resin adhesive.

[0035] Comparative Example 1

[0036] An epoxy resin adhesive was prepared according to the method of Example 1, except that 1-butyl-3-methylimidazolium trifluoromethanesulfonate was not added. The other conditions were the same as those of Example 1 to obtain an epoxy resin adhesive.

[0037] Comparative Example 2

[0038] An epoxy resin adhesive was prepared according to the method of Example 6, except that 1-butyl-3-methylimidazolium trifluoromethanesulfonate was not added. The other conditions were the same as those of Example 6 to obtain an epoxy resin adhesive.

[0039] Comparative Example 3

[0040] An epoxy resin adhesive was prepared according to the method of Example 1, except that the amount of 1-butyl-3-methylimidazolium trifluoromethanesulfonate was reduced to 1 part by mass, and the other conditions were the same as those of Example 1 to obtain an epoxy resin adhesive.

[0041] Comparative Example 4

[0042] An epoxy resin adhesive was prepared according to the method of Example 1, except that bisphenol F diglycidyl ether 806 was replaced by bisphenol F diglycidyl ether RF1320 in the same weight portion, and the other conditions were the same as in Example 1 to obtain an epoxy resin adhesive.

[0043] Test Case

[0044] The epoxy adhesives obtained in the above examples and comparative examples were tested for bonding performance, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following methods. The results are shown in Table 1.

[0045] (1) Bonding strength test before power on: Use a glue dispenser to dispense the epoxy adhesive obtained in the embodiment and the comparative example at 110°C, apply a 25mm*4mm rectangular glue line on the stainless steel substrate, and then bond another stainless steel substrate to the stainless steel substrate. After bonding, cure the sample in an environment of 165°C for 2h to obtain the sample to be tested. Use a universal material testing machine to run the sample to be tested along the shear direction at a speed of 10mm / min until the sample fails to bond, record the maximum force value displayed by the instrument, and calculate the shear bonding strength of the adhesive to the stainless steel substrate in combination with the bonding area.

[0046] (2) Bonding strength after power-on: After the glue is dispensed and cured according to the method in (1), the sample to be tested is obtained. The positive and negative wires of the DC power supply are clamped at the two ends of the sample respectively. The power is applied at a voltage of 48 V or 60 V for 30 min or 20 min. After the power-on is completed, the sample is removed and the sample to be tested is run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated based on the bonding area (when the bonding strength is less than 2 MPa, it is removable).

[0047] (3) Heat resistance (80°C): After curing the adhesive according to the method in (1), the sample to be tested was obtained. The bonded sample was placed in an oven at 80°C for 20 min. Then, a universal material testing machine was used to run the prepared bonding sample in an environment of 80°C at a speed of 10 mm / min along the shear direction until the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.

[0048] (4) High temperature and high humidity resistance (85°C, 85% RH): The test sample was obtained after curing by the method in (1). The bonded shear sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample failed to bond. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.

[0049] Table 1

[0050]

[0051] The dispersion effect of the inorganic filler can be reflected by the bonding strength without power supply. Under the same other conditions, if the inorganic filler is dispersed more evenly, the bonding strength without power supply is higher, and the heat resistance and moisture resistance are better, otherwise it is lower. It can be seen from the results of Table 1 that the epoxy resin adhesive provided by the present invention has a higher bonding strength when not powered, and the heat resistance and high temperature and high humidity resistance are both excellent, which can explain that the inorganic filler is dispersed more evenly. In addition, the bonding strength of the epoxy resin adhesive provided by the present invention can be reduced to less than 2MPa after power supply, that is, it has good detachable performance.

[0052] From the comparison between Example 1 and Comparative Example 1, Example 6 and Comparative Example 2, and Example 1 and Comparative Example 3, it can be seen that when no ionic liquid is added or the amount of ionic liquid is lower than the lower limit level of the present invention, the un-energized bonding strength and heat resistance of the obtained epoxy resin adhesive as well as the high temperature and high humidity resistance will be affected, and the bonding strength after energization still remains at a high level and cannot be reduced to below 2 MPa, that is, it does not have detachable properties.

[0053] From the comparison between Example 1 and Comparative Example 4, it can be seen that when the viscosity of the epoxy resin contained in the epoxy resin adhesive is higher than the upper limit level of the present invention, the un-energized bonding strength and heat resistance as well as the high temperature and high humidity resistance of the obtained epoxy resin adhesive will be affected, and the bonding strength after energization will still remain at a high level and cannot be reduced to below 2 MPa, that is, it does not have detachable properties.

[0054] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An epoxy resin adhesive, characterized in that: The epoxy resin adhesive contains epoxy resin, ionic liquid, coupling agent, inorganic filler and optional curing agent, color powder and additives. The viscosity of the epoxy resin at 25° C. is 1000-15000 cps. The mass ratio of the epoxy resin, ionic liquid, coupling agent and inorganic filler is 100:(20-200):(2-50):(120-600).

2. The epoxy resin adhesive according to claim 1, characterized in that The content of the epoxy resin is 10 to 25 parts by mass, the content of the ionic liquid is 5 to 20 parts by mass, the content of the coupling agent is 0.5 to 5 parts by mass, the content of the inorganic filler is 30 to 60 parts by mass, the content of the curing agent is 5 to 20 parts by mass, the content of the color powder is 0.1 to 5 parts by mass, and the content of the auxiliary agent is 0 to 20 parts by mass.

3. The epoxy resin adhesive according to claim 1, characterized in that: The epoxy resin is an aromatic epoxy resin and / or an aliphatic epoxy resin.

4. The epoxy resin adhesive according to claim 1, characterized in that: The melting point of the ionic liquid is below 25°C; Preferably, the ionic liquid is composed of organic cations and anions, the organic cations are selected from at least one of imidazole cations, pyrrole cations, quaternary ammonium salt cations, quaternary phosphonium salt cations, pyrrolidine cations and piperidine cations, and the anions are selected from at least one of trifluoromethanesulfonate anions, tetrafluoroborate anions, hexafluorophosphate anions, bisfluoromethanesulfonyl imide anions, hydrogen sulfate anions, ethyl sulfate anions and p-toluenesulfonate anions; Preferably, the ionic liquid is selected from 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-2,3-dimethylimidazolium trifluoromethanesulfonate, 1-octyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-2,3-dimethylimidazolium tetrafluoroborate, 1-propyl-2,3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-2,3-dimethylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide , 1,3-diethylimidazolium bis(trifluoromethanesulfonyl)imide, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide, N-butylpyridinium tetrafluoroborate, hexyltriethylammonium bis(trifluoromethanesulfonyl)imide, methyltrioctylphosphonium bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpyrrolidine trifluoromethanesulfonate and N-propyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide.

5. The epoxy resin adhesive according to claim 1, characterized in that: The coupling agent is selected from at least one of γ-aminopropyl triethylsiloxane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-methacrylate propyl trimethoxysiloxane, γ-thiopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane.

6. The epoxy resin adhesive according to claim 1, characterized in that: The inorganic filler is selected from at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talc powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder.

7. The epoxy resin adhesive according to claim 1, characterized in that: The curing agent is selected from at least one of an amine curing agent, an acid anhydride curing agent and an imidazole curing agent; Preferably, the toner is selected from at least one of carbon black, iron oxide toner, chromate toner, cadmium toner, ultramarine and phthalocyanine blue; Preferably, the auxiliary agent is selected from at least one of a defoamer, a leveling agent, a dispersant and an antioxidant.

8. The method for preparing the epoxy resin adhesive according to any one of claims 1 to 7, characterized in that: The method comprises the steps of uniformly mixing epoxy resin, ionic liquid, coupling agent, inorganic filler, and optional curing agent, color powder and auxiliary agent to obtain epoxy resin adhesive.

9. Use of the epoxy resin adhesive according to any one of claims 1 to 7 in bonding electronic products.